PENGARUH MODEL PROBLEM BASED LEARNING (PBL) DAN GROUP INVESTIGATION (GI) DALAM PEMBELAJARAN SEJARAH DITINJAU DARI MOTIVASI BELAJAR DI SMA MARTAPURA - Muhammad Dody Hermawan (ISTORIA: Jurnal Pendidikan dan Sejarah, 2018)
The purpose of this reaserch are (1) find differences influence model of Group Investigation (GI) and Problem Based Learning (PBL). (2) find differences influence learning motivation of students to critical thinking abilities of learners. (3) find the interaction effect between learning models and learning motivation of the critical thinking skills of learners. This study will be conducted in SMA Martapura, Banjar regency, South Kalimantan. Subjects of the study were students of class XI SMA Martapura academic year 2015/2016. This type of research to be carried out in this study is a quantitative study using experimental methods. Design of this research is 2 X 2 factorial design to data collection technique motivation questionnaire and tests critical thinking skills. The result, 1) There is a difference between the positive influence of the Model Group Investigation (GI) and Problem Based Learning (PBL). 2) There are differences positively influence the motivation of students to critical thinking ability of students in learning the history. 3) There are nointeractions influence student learning model and motivation for students' critical thinking skill There is no interaction effect Learning Model and the Motivation of students' critical thinking skills of students in Learning Historys. Keywords: PBL Models, GI Models, Learning Motivation